SOCIAL ENTREPRENEURSHIP - David Setiawan (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
This study aims to apply Paul's entrepreneurial characteristics as a form of Social Entrepreneurship for Christian entrepreneurs today. Researchers find that there is still little study of this matter so more in-depth research is needed. In addition, the existing studies generally only examine the extent of entrepreneurship. The authors used the research library and rhetorical criticism methods in this study to solve existing problems. The research problem that has been solved is applying Paul's entrepreneurial characteristics as a form of Social Entrepreneurship for Christian entrepreneurs today. The results of this study indicate that Christian entrepreneurs are social entrepreneurs who are required to be innovative, creative, brilliant in reading opportunities, helpful, and actively involved in social transformation, such as Paul's entrepreneurial characteristics.